PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN MASALAH BANGUN DATAR - Fatqurhohman, Fatqurhohman (Jurnal Ilmiah Pendidikan Matematika (JIPM), 2016)
This research is meant to describe the studentsâ understanding of Mathematics Concept related to non-routine problem in contour Shapes. This research is a qualitative research. The subject of this research are 25 students of fourth (VI) grade of SDN Mojorejo 02 Kota Batu. The data are collected through studentsâ response on a test given. Based on the result of this research shows that students are still unable to use Mathematics concept well in solving some problems (still tent to be procedural), students are still unable to compare by presenting alternative solution aside from response obtained, studentsâ mastery and understanding concept of Mathematics in solving non-routine questions are still low. Teachers are hoped to be able to provide non-routine questions in order to allow students to be accustomed with and develop ability in relation to problem solvingÂ Artikel ini bertujuan untuk mendeskripsikan pemahaman konsep matematika siswa kaitannya dengansoal non-rutin pada materi bangun datar. Jenis penelitian ini adalah kualitatif. Subjek penelitian adalah siswa kelas IV (empat) SDN Mojorejo 02 Kota Batu yang berjumlah 25. Data diperoleh melalui hasil respon/jawaban tes siswa. Berdasarkan hasil yang diperoleh bahwa siswa belum dapat dengan baik menggunakan konsep-konsep matematika dalam menyelesaiakan masalah (masih cenderung prosedural), siswa belum dapat membandingkan dengan menyajikan alternatif solusi yang lain dari respon yang diperoleh, penguasaan dan pemahaman konsep matematika dalam menyelesaikan soal non-rutin masih rendah. Diharapkan guru dapat memberikan soal non-rutin agar siswa terbiasa dan mengembangkan kemampuannya kaitannnya dengan pemecahan masalah.Â